Analysis of Income and Level of Satisfaction of Farmer Groups with UPPB OKU Regency - Septiana, A; Sari, Y; Sari, Fifian Permata; Julkhaidar, Julkhaidar (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
OKU Regency is a significant smallholder rubber-producing region, covering an area of 72,010 hectares as of 2023. The presence of UPPB (joint processing and marketing units) in OKU Regency has greatly facilitated local rubber farmers' marketing of Bokar. UPPB plays a crucial role in enhancing the income of rubber farmers in the region. This study investigates farmer groups' income levels and satisfaction associated with UPPB in OKU Regency. The research employs a survey method with a simple random sampling technique. It involves 77 rubber farmers from a total of 350 UPPB members in OKU. Conducted in November 2023, the study focuses on Peninjauan District, the central hub of UPPB activities and the rubber auction market in OKU. Data analysis is performed using a quantitative descriptive method, applying an income equation to evaluate the income of rubber farmers participating in the UPPB.